Pembelajaran Matematika Berorientasi Etnomatematika Rejang Lebong Di Prodi Sains Perkopian Universitas Pat Petulai - Tanti Novita; Dendi Septian Putra (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
This research aims to describe the results of ethnomathematics exploration of the Rejang Lebong community using exploratory research and an ethnographic approach. The research results show that without studying mathematical concepts, the Rejang Lebong people have applied these concepts in their daily lives using ethnomathematics. It is proven that there are mathematical concepts contained in traditional house buildings, decorative geometric shapes in rejang weaving, as well as traditional dances of the Rejang Lebong people. The researcher suggests the results of this research to: (a) be used as an alternative idea for learning mathematics outside the classroom, (b) be introduced to formal mathematics learning as initial capital for teaching mathematical concepts to Pat Petulai University coffee science study program students, (c) be used as reference material for compiling contextual mathematics problem solving questions.